2000
DOI: 10.1016/s0550-3213(99)00696-3
|View full text |Cite
|
Sign up to set email alerts
|

Non-conventional cosmology from a brane universe

Abstract: We consider "brane-universes", where matter is confined to four-dimensional hypersurfaces (three-branes) whereas one extra compact dimension is felt by gravity only. We show that the cosmology of such branes is definitely different from standard cosmology and identify the reasons behind this difference. We give a new class of exact solutions with a constant five-dimensional radius and cosmologically evolving brane. We discuss various consequences.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
1,224
2
3

Year Published

2000
2000
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 974 publications
(1,256 citation statements)
references
References 22 publications
27
1,224
2
3
Order By: Relevance
“…Of course, the FRW constraint in this braneworld context also comes with an unconventional term quadratic in ρ [4].…”
Section: Construction Of a Bouncing Braneworldmentioning
confidence: 99%
See 2 more Smart Citations
“…Of course, the FRW constraint in this braneworld context also comes with an unconventional term quadratic in ρ [4].…”
Section: Construction Of a Bouncing Braneworldmentioning
confidence: 99%
“…In this region, we have r * → ±∞ as r → r ∓ . Finally, it will be useful to work with null coordinates, 4) with which the line element becomes ds 2 = V (r)du dv + r 2 dΣ 2 k . The massive Klein-Gordon equation in the charged black hole background (2.2) may be expanded as…”
Section: Instability Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In general, effects arising from the extra dimensions in this setup will be incompatible with the observed behaviour of our universe. However, if a negative cosmological constant is added to the bulk, it is possible (to leading order) to reobtain standard four-dimensional gravity [1] and cosmology on the brane [2].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the Friedmann equation on the brane contains corrections to the usual four-dimensional equation. In particular a term H ∝ ρ was found [3]. This term is observationally problematic (e.g.…”
Section: Introductionmentioning
confidence: 99%